Proceso atención de enfermería en paciente con síndrome de inmunodeficiencia adquirida. - Duarte Jaña, Jefferson Jaime (2023)
Human immunodeficiency virus (HIV) infection is one of the main sexually transmitted infections (STIs) globally. For this reason, the following clinical case has been presented where we were able to assess a 55-year-old male patient with a diagnosis of acquired human immunodeficiency virus (HIV), with a clinical picture of gradual weight loss, diarrhea that cannot be controlled and fever that does not subside with antipyretics. After the presumptive diagnoses were established, laboratory confirmation was performed, which includes blood biochemistry, hematology, and immunology. After the definitive diagnosis was given, we were able to act appropriately together with the health team, where the medical work and the importance of the intervention of the nursing area for the restoration of the physical, emotional, work and family health of the patient are reflected. patient. Once diagnosed and treated, we began the Nursing Care Process by evaluating Marjory Gordon's functional patterns, where we were able to identify the dysfunctional patterns, which were compromising the patient, among them, we have the pattern: nutritional/metabolic, pattern: elimination/ exchange, pattern: adaptation / tolerance to stress, these were treated immediately by applying nursing care, managing to stabilize and restore the clinical picture that compromised the patient's health during his hospital stay. The patient was educated so that he attends his monthly follow-up checks and the withdrawal of his medication, as well as his psychological therapy for adaptation and successful reintegration into society. Afterwards, the pertinent nursing care will be carried out, where the use of the Nanda (diagnoses), Nic (interventions) and Noc (results) taxonomies was applied, with the purpose of achieving our objectives set out in our clinical case study.